The fetal matrix evolution, development, and disease - Gluckman, Peter D. (Cambridge University Press, 2005)
New discoveries reveal how crucial interactions which determine our destiny occur before birth, when our genes interact with their environment as the embryo and fetus develop. These processes - in the matrix of the womb - are evolutionary echoes of mechanisms which allowed our hunter-gatherer ancestors to survive. These exciting insights into predictive adaptive responses suggest new ways of protecting the health of the fetus, infant and adult. If inappropriate they can trigger obesity, diabetes and heart disease, formerly thought to result solely from adult lifestyle. The new concepts in this book are crucial to understanding the daunting public health burden in societies undergoing rapid transition from poverty to affluence. They add an important new dimension to evolutionary theory. Synthesising developmental biology, evolutionary history, medical science, public health and social policy, this is a ground-breaking and fascinating account by two of the world's leading pioneers in this important emerging field.